Faktor-faktor yang Berpengaruh terhadap Pengambilan Nilai Pembiayaan Murabahah - Rusydiana, Nina; Ali, A.M. Hasan (Faculty of Shariah and Law, 2012)
In economic aspect, the existence of home industry gives subtantial impact on the economy of a village. Tofu is one of potential household scale industries developed in Indonesia. In running their business, the producers also has disadvantages like the availability of sufficient capital to balanced the ability to repay the loan in accordance with its characteristics. One solution to solve this is by giving murabahah finance. Research refeals that the factors that influence the decision value murabahan financing to tofu producers are value of instalments, number of instalments, the amount of the worker and the capital value of the coefficient of determination value contribution is 0.705.DOI: 10.15408/aiq.v4i1.2085